Pemanfaatan Bahan Alam Sebagai Alat Permainan Edukatif di Kelompok B TK Se-Kecamatan Selupu Rejang Kabupaten Rejang Lebong Provinsi Bengkulu - Salsabila, Alya Salsabila; Suryadi, Didik; D, Delrefi (UNIB Press, 2022)
This study aimed to describe the use of natural materials as educational game tool in learning. The population of this study were all 56 teachers. The sampling of this study used a total sampling technique so that all populations were sampled. The data collection techniques of this research used a questionnaire. The data were analyzed by using the average and percentage formula. The results of the research showed that the use of natural materials as educational game tool are categorized as very low. In the aspect of the types of natural materials, the characteristics of educational game tool and the types of natural materials used in a month are categorized as very low, while the educational game tool requirements are categorized as low. The results of research in group B Kindergarten in Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province showed that teachers still verry rarely used natural materials as educational game tool.